2020
DOI: 10.5114/ceh.2020.102172
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic interferon γ and tumor necrosis factor a expression in infants with neonatal cholestasis and cytomegalovirus infection

Abstract: Aim of the study:To determine the hepatic interferon γ (IFN-γ) and tumor necrosis factor a (TNF-a) levels in infants with neonatal cholestasis (NC) and associated cytomegalovirus (CMV) infection. Material and methods: This study was conducted in 21 infants with NC over a period of 6 months from June 2017 to December 2017 to determine the hepatic IFN-γ and TNF-a levels in infants with NC and associated CMV infection. Results: IFN-γ levels were positive in 16 (80%), low positive in 3 (16%) and negative in 1 (5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Finally, a total of 19 studies published from 1980 to 2020, which met the eligibility for data extraction and analyses were used for the quantitative synthesis; nine studies from Asia, five studies from Europe, four studies from the Americas, and a study from Africa. 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 The main characteristics of these included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 19 studies published from 1980 to 2020, which met the eligibility for data extraction and analyses were used for the quantitative synthesis; nine studies from Asia, five studies from Europe, four studies from the Americas, and a study from Africa. 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 The main characteristics of these included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, inflammatory cytokines play a vital role in the process of hepatic fibrosis of biliary atresia. In BA patients and BA model rats, IL-6, IL-1 β , and TNF- α significantly increased [ 21 , 22 , 23 ]. In the process of liver injury, IL-6 is released from bile duct epithelial cells, which directly promotes cell regeneration and proliferation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cholestasis in term infants is a rare condition of different causes where biliary atresia is the most common (11). CMV has been associated with biliary atresia and other cholestatic conditions in infancy (12)(13)(14)(15)(16). In preterm infants, cholestasis is far more common than in term infants, and the condition is related to prolonged parenteral nutrition, often due to feeding intolerance secondary to bowel disease such as NEC with subsequent intestinal failure (17)(18)(19), but the potential importance of CMV in this condition is not well-investigated.…”
Section: Introductionmentioning
confidence: 99%